Santorini : volcano, natural history, mythology (Aarhus University Press, 2009)
3 The geological development of SantoriniNon-volcanic rocks; Volcanic rocks and their deposition; 4 Stratigraphy -- the backbone of geology; Paleontological remains; Marine fossils of the Profitis Elias; Marine fossils at Archangelos Vouno; Absolute dating; Dating of organic remains; Tephrochronology; 5 Plant remains and geological time; Plant fossils in volcanic regions; The plant fossils of Santorini; Plant remains of the Fira Beds; Plant fossils on Therasia; Plants as indicators of climate; The flora of Santorini today; II The Minoan eruption; 6 The mechanism of the Minoan eruption